Differences Of Mathematical Reasoning And Communication Ability Teached With STAD And Group Investigation Learning - Ginting, Najamuddin Al Amin (Yana Research, 2022)
This study aims to find out whether there are differences in students' mathematical reasoning and communication abilities taught with the STAD and GI models in class X MAN Binjai in the 2020/2021 academic year. this research is quantitative research. The samples in this study were students of class X IPA 1 and X IPA 2 with a total sample of 63 students. To find out the reasoning and communication skills of students, a test in the form of a description is used. data analysis was carried out by analysis of variance (ANAVA). The findings show: 1). there is a significant difference in the reasoning ability of students taught by the STAD and GI models with F count (10,466)> F table (3,998) at an alpha level of 0.05 ,2). There is a significant difference in students' mathematical communication skills taught by the STAD and GI models with F count (6.237) > F table (3.998) with an alpha level of 0.05. The conclusion of this study explains that students' mathematical reasoning and communication skills are better taught using the GI model than the STAD model.